2022
DOI: 10.1186/s12866-022-02592-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of planting of two common crops, Allium fistulosum and Brassica napus, on soil properties and microbial communities of ginseng cultivation in northeast China

Abstract: Background Long-term cultivation of ginseng can cause severe crop disorders and soil sickness. Crop rotation is an effective agricultural management measure to improve soil sustainability and decrease pathogens. However, the suitable ginseng rotation system and the changes in soil microbial community and soil characteristics under the rotation system need to be further explored. Methods To explore suitable ginseng crop rotation systems and improve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…The nitrogen conversion rate is closely related to the soil nitrogen content [19], and there is a significant correlation between the content of ammonium nitrate nitrogen. A reasonable crop rotation pattern can lead to a significantly increase the abundance of microbes and activity of enzymes related to soil nitrogen transformation, therefore significantly promoting soil nitrogen transformation and maintaining high levels of soil inorganic nitrogen content [6,8]. This study also emphasizes the importance of adding one or more crops to the nitrogen cycle, as they provide carbon and nitrogen inputs and affect nitrogen transformation and migration in the soil through the decomposition and mineralization processes of different nitrogen-containing organics [38].…”
Section: Soil Nitrogen Transformationmentioning
confidence: 84%
See 1 more Smart Citation
“…The nitrogen conversion rate is closely related to the soil nitrogen content [19], and there is a significant correlation between the content of ammonium nitrate nitrogen. A reasonable crop rotation pattern can lead to a significantly increase the abundance of microbes and activity of enzymes related to soil nitrogen transformation, therefore significantly promoting soil nitrogen transformation and maintaining high levels of soil inorganic nitrogen content [6,8]. This study also emphasizes the importance of adding one or more crops to the nitrogen cycle, as they provide carbon and nitrogen inputs and affect nitrogen transformation and migration in the soil through the decomposition and mineralization processes of different nitrogen-containing organics [38].…”
Section: Soil Nitrogen Transformationmentioning
confidence: 84%
“…Prior research indicated that an appropriate crop rotation system reduced the accumulation of mineral nitrogen in soil and reduced the loss of gaseous nitrogen or the leaching of nitrate nitrogen during the denitrification process [6,7]. Significant differences were observed in soil nitrogen components, microbial biomass, and soil enzyme activities under different crop rotation patterns [8][9][10]. After crop rotation, soil organic matter, microbial biomass carbon, and nitrogen content were significantly increased, and soil enzyme activities were enhanced, which was beneficial to maintaining soil fertility and productivity [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Tang et al [7] demonstrated the ability of the mixed cropping of apple trees with A. fistulosum L. to alleviate apple replant disease. Similarly, Bian et al [8] showed the beneficial effects of A. fistulosum planted with ginseng cultivation as well as the positive impact of and A. fistulosum cultivation in reducing soil salinity. When considering seed quality issues, to date there is still poor attention on Welsh onion.…”
Section: Introductionmentioning
confidence: 91%
“…Finally, the function of soil microorganisms in each group was predicted. Soil bacterial functions were predicted using the PICRUSt tool based on 16S rRNA sequencing data, and biological functions were annotated in the KEGG database (Bian et al 2022;Gong et al 2021). Furthermore, the FUNGuild tool was used for the functional prediction and classi cation of soil fungi (Schmidt et al 2019).…”
Section: Bioinformatic Analysismentioning
confidence: 99%